A Mapping Outcome Method Using Social Return on Investment (SROI) to Assess the Impacts of Program: A Case Study in Setunak Island - Retno Suryani; Nugroho Budi Susilo; Ode Arinal Desta; Andriani Silfiana; Rina Wulansari; Annisa Sila Puspita (Universitas Diponegoro, 2023)
Climate change as a global phenomenon is inevitable, including in Indonesia. Its impacts include rising sea levels, expanding coral bleaching, and declining coastal ecosystems, particularly mangrove forests and coral reefs. Many research explores the characteristics of vulnerability to climate change in coastal cities and seeks feasible adaptation options for these cities with method used involved surveys of residents, interviews with experts, and statistical analysis and modeling. Although efforts have been made to prevent climate change, there is still a lack of research that explores the broader impacts of these efforts. In this regard, few studies have measured the social, economic, or environmental value that arises from these efforts. This study aims to evaluate, measure, and assess the impacts that have occurred as a result of the implementation of the program from environmental, economic, welfare, and social perspectives comprehensively. The result show that the SROI study results indicate that the Pulau Tahan program has positive economic, social, and environmental impacts. However, the on-field study also found a less positive fact regarding the availability of crab seedlings.